The effect of supplemental biotin in dairy cow diets on forage fermentation characteristics - Bunge, Gregory Andrew (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MscAgric (Animal Sciences))--University of Stellenbosch, 2006.